Economic viability of a monitoring system in mechanized citrus production - Da Silva, Josivan Alves; Santos, David Ferreira Lopes [UNESP]; Vidal, Diego Onofre [UNESP]; Da Silva, Rouverson Pereira [UNESP]; Montoro, Stela Basso [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
Digital agriculture is currently the main technological paradigm in agribusiness, in which one of the main challenges is the convergence of new monitoring technologies with the management of the volume of infor-mation generated to increase productivity. This research analyzes the economic viability of a monitoring system deployed on eight tractors and two trucks used for spraying operations in a citrus farm. The operations covered an area of 2,236 ha and were performed during the 2016/2017 harvest. The economic results of the investment were examined using the discounted cash flow method associated with the Monte Carlo simulation. The monitoring system provided greater availability and quality of information, which improved the quality of operations management. The results pointed to 23.67% lower costs per hectare in monitored compared to unmonitored areas. Economic analysis demonstrated the viability of the investment with 99.5% confidence, whose gain in Net Present Value per machine represents 15% of the machine acquisition cost. The results of this study are pioneering for mechanized citrus operations and denote the importance of investments in automated digital monitoring systems that allow better monitoring of management activities in orange production.
Keywords: Agribusiness; Digital agriculture; Monitoring system; Monte Carlo simulation; Plant health; Spraying.